Cardiac Preload Responsiveness in Children With Cardiovascular Dysfunction or Dilated Cardiomyopathy. Issue 1 (January 2015) - de la Oliva, Pedro; Menéndez-Suso, Juan J.; Iglesias-Bouzas, Mabel; Álvarez-Rojas, Elena; González-Gómez, José M.; Roselló, Patricia; Sánchez-Díaz, Juan I.; Jaraba, Susana
<x xml:space="preserve">Abstract</x> Objectives: To characterize cardiac preload responsiveness in pediatric patients with cardiovascular dysfunction and dilated cardiomyopathy using global end-diastolic volume index, stroke volume index, cardiac index, and extravascular lung water index. Design: Prospective multicenter observational study. Setting: Medical/surgical PICUs of seven Spanish University Medical Centers. Patients: Seventy-five pediatric patients (42 male, 33 female), median age 36 months (range, 1–207 mo), were divided into three groups: normal cardiovascular status, cardiovascular dysfunction, and dilated cardiomyopathy. Interventions: All patients received hemodynamic monitoring with PiCCO2 (Pulsion Medical System SE, Munich, Germany). We evaluated 598 transpulmonary thermodilution sets of measurements. In 40 patients, stroke volume index, cardiac index, and global end-diastolic volume index were measured before and after 66 fluid challenges and loadings to test fluid responsiveness at different preload levels. Measurements and Main Results: Global end-diastolic volume versus predicted body surface area exhibits a power-law relationship: Global end-diastolic volume = 488.8·predicted body surface area1.388 (r2 = 0.93). Four levels of cardiac preload were established from the resulting "normal" global end-diastolic volume index (= 488.8·predicted body surface area0.388). Stroke volume index and cardiac index versus global end-diastolic volume index/normal global end-diastolic volume index built using a linear mixed model analysis emulated Frank-Starling curves: in cardiovascular dysfunction group, stroke volume index (geometric mean [95% CI]) was 27 mL/m2 (24–31 mL/m2) at "⩽ 0.67 times normal global end-diastolic volume index, " 37 mL/m2 (35–40 mL/m2) at "> 0.67 ⩽ 1.33 times normal global end-diastolic volume index" (Δ stroke volume index = 35%; p < 0.0001; area under the receiver-operating characteristic curve = 75%), 45 mL/ m2 (41–49 mL/m2) at "> 1.33 ⩽ 1.51 times normal global end-diastolic volume index" (Δ stroke volume index = 21%; p < 0.0001; area under the receiver-operating characteristic curve = 73%), and 47 mL/m2 (43–51 mL/m2) at "> 1.51 times normal global end-diastolic volume index" (Δ stroke volume index = 4%; p = 1; area under the receiver-operating characteristic curve = 54%). In dilated cardiomyopathy group, stroke volume index was 21 mL/m2 (17–26 mL/m2) at "> 0.67 ⩽ 1.33 times normal global end-diastolic volume index, " 27 mL/m2 (21–34 mL/ m2) at "> 1.33 ⩽ 1.51 times normal global end-diastolic volume index" (Δ stroke volume index = 29%; p = 0.005; area under the receiver-operating characteristic curve = 64%), and 25 mL/m2 (20–32 mL/m2) at "> 1.51 times normal global end-diastolic volume index" (Δ stroke volume index = –8%; p = 1; area under the receiver-operating characteristic curve = 54%). Conclusions: This study provides "normal" values for global end-diastolic volume index and limits of cardiac preload responsiveness in pediatric patients with cardiovascular dysfunction and dilated cardiomyopathy: 1.33 times normal global end-diastolic volume index represents the upper limit of patent cardiac preload responsiveness, with the highest expected responsiveness being below 0.67 times normal global end-diastolic volume index. The maximum response of the Frank-Starling relationship and therefore the level of no additional preload reserve is 1.33 to 1.51 times normal global end-diastolic volume index. Above 1.51 times normal global end-diastolic volume index preload responsiveness is unlikely, and the risk of pulmonary edema is maximal.